High levels of chronic immune activation in the T-cell compartments of patients coinfected with hepatitis C virus and human immunodeficiency virus type 1 and on highly active antiretroviral therapy are reverted by alpha interferon and ribavirin treatment - Gonzalez, Veronica D; Falconer, Karolin; Blom, Kim G; Reichard, Olle; Mørn, Birgitte; Laursen, Alex Lund; Weis, Nina; Alaeus, Annette; Sandberg, Johan K (Journal of virology, 2009)
Chronic immune activation is a driver of human immunodeficiency virus type 1 (HIV-1) disease progression. Here, we describe that subjects with chronic hepatitis C virus (HCV)/HIV-1 coinfection display sharply elevated immune activation as determined by CD38 expression in T cells. This occurs, despite effective antiretroviral therapy, in both CD8 and CD4 T cells and is more pronounced than in the appropriate monoinfected control groups. Interestingly, the suppression of HCV by pegylated alpha interferon and ribavirin treatment reduces activation. High HCV loads and elevated levels of chronic immune activation may contribute to the high rates of viral disease progression observed in HCV/HIV-1-coinfected patients.